Identifikasi Cendawan Patogen pada Tanaman Sorgum di Timor Tengah Utara - Aloysius Rusae; Bernadina Metboki; Blasius Atini (Savana Cendana, 2018)
Sorghum is a local plant in North Central Timor (TTU). The presence of sorghum disease is unknown in this area. This study aimed to identify pathogenic fungi that attack sorghum plants in North Central Timor District, East Nusa Tenggara Province. The experimental study was conducted with a Randomized Block Design (RBD). The treatment consisted of 4 varieties of sorghum namely (V1) local varieties red, (V2) local white, (V3) local black, and (V4) Numbu. of the treatment was repeated 3 times so that there were 12 experimental plots. Observation of disease and pathogen identification using morphological characters. The results showed the diseases that attack the sorghum plants were leaf blight, stem rot, and rust leaf. The intensity of disease incidence is 4.25% - 51.17% and the severity of the disease is 60.68-83.73%. Stem rot disease caused by Rhizoctonia sp. could infect all varieties of Sorghum but not caused disease severity. Rust disease infected Local White and Local Red varieties, with the highest disease severity was found in White Local varieties (83.73%). On the other hand, leaf blight disease caused by Helmithosporium sp was found only in Black and Numbu Local varieties with the highest disease severity in Numbu varieties Lokal Merah Lokal Merah Lokal Merah Lokal Merah Lokal Merah Lokal Merah (49.60%).